Penerapan Pembelajaran Tematik Berbasis TIK di Sekolah Dasar - Nur Azizah; Rika Delima; Mila Karmelia; Adyanata Lubis (Universitas Muria Kudus, 2021)
In the 2013 curriculum learning inelementary schools has implemented integrated thematic learning.meaning that the learning material presented is an integration and various subjects are packaged in an integrated manner using themes and sub-themes as unifying learning. Learning media thematic is a bridge between learning materials that must be adjusted to the needs of the characteristics of elementary school students who still think concretely and combine various concepts in one study into the themes contained in the media. Information and communication technology is a medium for carrying out activities such as processing, managing, and, transferring information with the principle of using ICT effectively, efficiently, attracting and stimulating creativity. ICT is one of the learning media that is widely usedin various fields of education because it increases effectiveness andefficiency in the learning process.Â Â